Public Policy Analysis of Health System in Conditions of the Greek Economic Crisis - Farantos, Georgios I.; Koutsoukis, Nikitas Spiros (European Scientific Journal, ESJ, 2017)
The aim of the study is to provide a literature overview of the Public Policy Analysis of the Greek Health System during the Economic Crisis, so that the generated knowledge can be used in Doctoral studies. The research methodology extends to the literature overview of valid Greek and international literature. The Findings of the study include summarising and categorising information related to the categories of public policies and those involved in policy making. Studies on policy changes in conditions of an economic crisis are reviewed. The Policy Change in the Greek Health System during the economic crisis is studied and placed within a pre-existing framework for classification of health system policies. Study limitation. The study specialises in the policy of the Greek Health System during the Economic Crisis and cannot be generalised as such for health systems of other countries. The study’s practical applications are that it may constitute a useful literature review for students who want to study the Policy of the Greek Health System during the Economic Crisis and it also leaves room for further future study of this field. Value. The present study is an innovative research, it is a source of collected information and offers practical help in the study of the field.